Stock Study of Bali Sardinella Fisheries at Pengambengan Nusantara Fishing Port, Bali - Sari, Iya Purnama; Satyawan, Noar Muda; Rahayu, Siti Mira (Journal of King Abdulaziz University: Marine Sciences, 2024)
Stock assessment is one of the efforts to see the impact and influence of fishing activities on fish stocks and populations. One of the fishery resources that has important economic value in Indonesia is Bali sardinella fisheries. The high production of Bali sardinella fisheries at the Pengambengan Nusantara Fishing Port (NFP) encourages an increase in intensity and catch effort, so it is feared that overexploitation may occur. This study uses primary data and secondary data from Pengambengan NFP, to analyze the level of effort, catch, and economic rent of Bali sardinella fisheries under MSY, MEY, and OA conditions. The result of the linear equation CPUE = -0.00008f + 3.1053, if the capture effort is increased it will reduce the CPUE value, and vice versa. The regression results of the Schaefer Model obtained EMSY results of 4,691 trips per year, MSY of 17,639 tons per year, and TAC of 14,111 tons per year. The results of the bioeconomic model prediction obtained EMEY and MEY values, namely 4,554 trips per year and 17,624 tons per year.